Genetic factors associated to development of thrombocytopenia in preeclampsia. - Córdoba-García, Santiago (2022)
Preeclampsia is a hypertensive disease that occurs after the 20 weeks of pregnancy, it is characterized by causing damage to various organs of the human body, mainly the liver and kidney, for this reason, it will be evidenced in laboratory tests: proteinuria, increased liver enzymes, hemolysis, oliguria, increased creatinine levels, thrombocytopenia, etc. The finding of thrombocytopenia during pregnancy always raises concern for clinicians due largely to the multiplicity of etiologies that must be considered to make a diagnosis. This topic review aims to analyze the presence of genetic factors that predispose or influence the development of thrombocytopenia in women with preeclampsia, highlighting to the reader the importance of prenatal controls in the prevention of diseases in pregnancy, keeping in mind risk factors associated with the development of pathologies in maternal and carry out the appropriate treatment to avoid complications in the gestation period. A literature search was conducted in the MedLine (PubMed), Clinical Key, and Science Direct databases, without restriction in time or language, considering the articles that described the diagnostic aspects, the genetic factors involved in the development of thrombocytopenia in preeclampsia, obtaining 57 articles after their selection process.